2011
DOI: 10.1261/rna.2452111
|View full text |Cite
|
Sign up to set email alerts
|

The stoichiometry of the Escherichia coli Hfq protein bound to RNA

Abstract: The Escherichia coli RNA binding protein Hfq is involved in many aspects of post-transcriptional gene expression. Tight binding of Hfq to polyadenylate sequences at the 39 end of mRNAs influences exonucleolytic degradation, while Hfq binding to small noncoding RNAs (sRNA) and their targeted mRNAs facilitate their hybridization which in turn effects translation. Hfq binding to an A-rich tract in the 59 leader region of the rpoS mRNA and to the sRNA DsrA have been shown to be important for DsrA enhanced translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 60 publications
4
40
0
Order By: Relevance
“…A differnce in binding stoichiometries observed in various methods and experiment conditions has been reported. A 2:1 Hfq 6 :DsrA binding ratio has been observed at submicromolar Hfq 6 concentrations (Lease and Woodson 2004;Mikulecky et al 2004;Sun and Wartell 2006), while 1:1 stoichiometry has also been reported (Brescia et al 2003;Hwang et al 2011;Updegrove et al 2011). Our knowledge is still very limited due to the lack of atomic resolution structural information.…”
Section: The Cooperation Of Hfq Hexamers In Binding Dsramentioning
confidence: 74%
See 3 more Smart Citations
“…A differnce in binding stoichiometries observed in various methods and experiment conditions has been reported. A 2:1 Hfq 6 :DsrA binding ratio has been observed at submicromolar Hfq 6 concentrations (Lease and Woodson 2004;Mikulecky et al 2004;Sun and Wartell 2006), while 1:1 stoichiometry has also been reported (Brescia et al 2003;Hwang et al 2011;Updegrove et al 2011). Our knowledge is still very limited due to the lack of atomic resolution structural information.…”
Section: The Cooperation Of Hfq Hexamers In Binding Dsramentioning
confidence: 74%
“…1A) is believed to bind to the proximal side on Hfq (Brescia et al 2003;Updegrove et al 2011), our crystal structure suggests that AU 6 A (28;35 nt on DsrA), which is a part of DsrA DII , inserts its 59-end A28 into the R site on the distal face of another Hfq hexamer (Fig. 3A).…”
Section: Au 6 a Binding Is Uniquementioning
confidence: 76%
See 2 more Smart Citations
“…19 In vivo DsrA·rpoS duplex formation at low temperature further requires the CsdA helicase, 20 and creates RNase III cleavage sites within the duplex that prevents reuse of DsrA. 21 DsrA was shown to bind with a 1:1 stoichiometry on the proximal face of Hfq, 8,22 whereas rpoS mRNA is recruited to At low temperatures the Escherichia coli rpoS mRNA, encoding the stationary phase sigma factor Rpos, forms an intramolecular secondary structure (iss) that impedes translation initiation. Under these conditions the small RNA DsrA, which is stabilzed by hfq, forms a duplex with rpoS mRNA sequences opposite of the ribosome-binding site (rbs).…”
Section: Introductionmentioning
confidence: 99%